Maturation of Normal Primate White Matter: Computed Tomographic Correlation - Quencer, Robert M. (American Journal of Neuroradiology, 1982)
Five infant baboons were examined with computed tomography (CT) during the first year of their lives to determine the rate and degree of normal white matter maturation in frontal, occipital, and parietal areas. The increase in CT numbers with age was correlated with gross and histologic specimens. Two phases of maturation were identified: a rapid phase (first 8–12 weeks) and a gradual phase (after 12 weeks). Frontal white matter was the most immature in the immediate postnatal period but it became equal in attenuation to the other regions by 4 weeks of age. Knowledge of white matter maturation rates may be particularly useful in cases of neonatal hypoxia/ischemia where zones of periventricular hypodensity are identified. The failure of such regions to follow a normal rate of maturation may indicate damage to the white matter and have significant prognostic implications.